Digging for Fire: Finding Control on the Australian Continent. (30th May 2018) - Neale, Timothy
Abstract : In this paper, I examine recent influential accounts of the bushfire knowledge and practicesof Aboriginal peoples and their ancestors on the Australian continent, drawingattention to how these accounts accord with problematic and ecomodernist aspects ofcontemporary bushfire management discourse. Developing a two-part critique of thisdiscourse, I suggest both that we should accord the ecological contributions of Aboriginalpeoples and their ancestors significantly greater esteem, and that the recent accountspotentially limit the grounds for contemporary Aboriginal peoples' engagements in themanagement of their territories or "Country".